2006
DOI: 10.1007/bf02912914
|View full text |Cite
|
Sign up to set email alerts
|

Serum alpha-2-macroglobulin, antitrypsin and antichymotrypsin activities in patients receiving treatment with cyclosporine

Abstract: Cyclosporine has been reported to function as an inhibitor of the chymotrypsin like activity of proteasome. We hypothesized that the administration of an exogenous proteinase inhibitor may affect the activities of the Serum antiproteinase activities of serum alpha 2 macroglobulin (AMG), alpha 1-antitrypsin (AT) and alpha 1-antichymotrypsin (ACT) were found to be altered in renal transplant patients receiving cyclosporine. KEY WORDS Alpha-2-macroglobulin,alpha-1-antitrypsin,alpha antichymotrypsin,C2, cyclospori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Several studies have shown that hepatic production of AAT is affected by several relevant drugs. CSA reduces AAT production in kidney transplantation [21]. Corticosteroids abrogate the inflammatory trigger required for AAT expression, with the exception of a narrow range of low-dose dexamethasone (DEX) that, much like cortisol, induces AAT expression [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that hepatic production of AAT is affected by several relevant drugs. CSA reduces AAT production in kidney transplantation [21]. Corticosteroids abrogate the inflammatory trigger required for AAT expression, with the exception of a narrow range of low-dose dexamethasone (DEX) that, much like cortisol, induces AAT expression [22].…”
Section: Introductionmentioning
confidence: 99%